(untitled) (Pedagogy of Higher and Secondary Education, 2007)
In the article is marked, that educational activity is most valuably carried out in developing studies during realization of the problem going near studies. Basic knowledges and abilities of future teacher of the mother tongue are selected at application of problem method of studies.